The effects of Coleus scutellarioides extract on physicochemical and antioxidant properties of fish gelatin active films - Fahimeh Hematian; Homa Baghaie; Abdorreza Mohammadi Nafchi; Marzieh Bolandi (Journal of Food and Bioprocess Engineering, 2022)
Active films are the new generation of packaging in the food industry that can maintain and develop the shelf life of food products. The aim of this study was to fabricate and characterize an antioxidant film using fish gelatin and Coleus scutellarioides extract (CSE). The CSE was added to the gelatin film solutions in three levels (10, 20, and 30 mL from the extract to 100 mL film solution). The results showed that increasing the extract level increased the thickness of films, and water vapor permeability decreased significantly (p < 0.05). The addition of CSE had no significant effect on the moisture content of films. Based on SEM images and FTIR spectra, the fabricated active films have a uniform and uneven structure and fracture were observed in the film structure at high levels of CSE. Chemical bonds were established between the protein-polymer and the phenolic compounds of extract. The incorporation of the CSE also increased the total phenol content, and the antioxidant activity of films and the highest amounts of them were observed in the sample containing the highest level of extract (28.73 mg GA/g of film and 83.24%, respectively). In summary, fish gelatin films containing CSE have the potential to be used as active packaging to extend the shelf life of food products.